Observatório CONTECSI e observatório do mercado de trabalho do profissional da informação: colaboração académica e científica FEA USP e ECA USP - Paletta, Francisco Carlos (2019)
The International Conference on Technology and Information Organization is an initiative of the "Observatory of the Labor Market in Information and Documentation" research group (OMTID - CNPq) of the School of Communications and Arts of the University of São Paulo. The TOI take place in academic and scientific collaboration with the CONTECSI FEA-USP, bringing together Information Science researchers, students and professionals - Librarianship, Archival Science and Museology, with the goal of promoting reflection and dialogue about relevant topics, as well as contributing to the integration of the academic and the professional environments, strengthening the interest in research, and sharing knowledge about the most innovative practices in this area.